Fourteen-year analysis of rugby injuries in a pediatric emergency department - Veronica Baioccato; Silvia Paronuzzi; Marco Bazo; Emanuele Zanardo; Viola Sattin; Giulia Lorenzoni; Dario Gregori; Andrea Ermolao; Silvia Bressan (Italian Journal of Pediatrics)
Abstract Background Rugby is the third most played contact team sport worldwide. Its growing popularity is raising concerns about injuries rates, given its collision-based nature and minimal use of protective gear. However, research on rugby injuries in Italy, especially in the pediatric age group, remains limited. Methods This retrospective study examined the visits of patients with rugby-related injuries presenting to a tertiary-care Pediatric Emergency Department (PED) in the Veneto region of Italy, which is the Italian region with the highest rate of youth rugby participation. Results The data of 928 PED admissions for rugby-related injuries were extracted from the electronic PED medical records between 2007 and 2021, and analyzed for demographics, injury characteristics and outcomes. Rugby-related injuries accounted for 0.3% of total PED visits (total admissions: 306,508). Injuries to the upper limbs were the most common (40.8%), with contusions being the most frequent diagnoses (34.7%). Concussions accounted for 12.6% of all injuries. The most common injury mechanism was contact with another player (71%). Most injuries were minor, resulting in discharge to home in 97% of cases, while only 3% required hospitalization. Conclusions This study provides insights into pediatric rugby injuries in the Italian setting. Our findings highlight the importance of prevention strategies for concussion and upper limb injuries. Further research is warranted to adopt evidence-based interventions for reducing the burden of rugby-related injuries in children and youth.